Safe-Deposit Box Using Fingerprint and Blynk - Yulianto Yulianto; Budi Juarto; Ika Dyah Agustia Rachmawati; Risma Yulistiani (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
The criminal act of robbery really makes people nervous, especially in urban areas. There are many ways that can be done to avoid robbery at home and office, such as increasing the security system in the house to protect valuables. Safe-deposit boxes are items that are used to store valuables. Safe-deposit box is used to prevent against theft who want to take valuable things. To increase security, technology has begun to develop for security in various ways, such as fingerprints, passwords, and buzzers. This research will focus on a safe security system using a fingerprint that is connected to the internet with the Blynk application so that the user will get a safe notification when the servo condition is open or closed. The fingerprint sensor is an access to open doors, the Arduino Uno microcontroller is a storage for command logic on the system, the stepper motor acts as an activator for opening and closing servo and the Esp8266 module as a Wi-Fi module that connects equipment components using the internet network with the Blynk application which is used as distance control and notification of incoming access to homes with the concept of Internet of Things (IoT).